The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11368-009-0145-2
|View full text |Cite|
|
Sign up to set email alerts
|

Cleanup of atrazine-contaminated soils: ecotoxicological study on the efficacy of a bioremediation tool with Pseudomonas sp. ADP

Abstract: Purpose To mitigate the environmental effects of atrazine, one of the cleanup strategies available is based on the use of atrazine-degrading bacteria. This work aimed to evaluate the efficacy of a previously developed bioremediation tool for atrazine-contaminated soils (combining bioaugmentation with Pseudomonas sp. ADP, hereafter designated as P. ADP, and biostimulation with citrate) on both soil habitat and retention functions, by performing ecotoxicological tests with standard soil and aquatic species. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 35 publications
6
31
0
Order By: Relevance
“…In agreement with previous studies, this would indicate an important environmental impact of the treatment of the contaminated soils with the bioremediation tool [14], [15], [18]. However, contrarily to what is reported for the case of soils contaminated with Atrazerba FL ([14], and present work), the eluates prepared from the soils spiked with Primextra S-Gold and subsequently treated with the ATZ-degrading bacterium plus citrate remained significantly toxic to the microalgae P. subcapitata in the time-frame of the biodegradation experiments. Based on experimental evidences, we propose that the high ecotoxicity of these eluates may be mainly associated with the presence of S -MET that remained in the soil and/or of its degradates, as is further discussed below.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous studies, this would indicate an important environmental impact of the treatment of the contaminated soils with the bioremediation tool [14], [15], [18]. However, contrarily to what is reported for the case of soils contaminated with Atrazerba FL ([14], and present work), the eluates prepared from the soils spiked with Primextra S-Gold and subsequently treated with the ATZ-degrading bacterium plus citrate remained significantly toxic to the microalgae P. subcapitata in the time-frame of the biodegradation experiments. Based on experimental evidences, we propose that the high ecotoxicity of these eluates may be mainly associated with the presence of S -MET that remained in the soil and/or of its degradates, as is further discussed below.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, these results together with indications from the chemical data that, in the time-frame of the biodegradation experiments, deethylatrazine (DEA) and deisopropylatrazine (DIA) did not accumulate in the soils (data not shown), point to a significant potential reduction in the dispersion of the herbicide and of its highly toxic N-dealkylated metabolites into the adjacent water compartments, as reported before [14]. In agreement with previous studies, this would indicate an important environmental impact of the treatment of the contaminated soils with the bioremediation tool [14], [15], [18]. However, contrarily to what is reported for the case of soils contaminated with Atrazerba FL ([14], and present work), the eluates prepared from the soils spiked with Primextra S-Gold and subsequently treated with the ATZ-degrading bacterium plus citrate remained significantly toxic to the microalgae P. subcapitata in the time-frame of the biodegradation experiments.…”
Section: Discussionsupporting
confidence: 75%
“…direct assays with soil organisms or physical and chemical scrutiny [20][21][22][23][24][25][26][27][28][29]. This study is part of a broader research project [REFUSE (III/AMB/2/2005), I.I.I., Portugal] that investigated the link and interdependency between structural and functional effects of pesticides in agricultural soils.…”
Section: Chlorpyrifos (Organophosphorus) Oo-diethyl O-(346-trichlomentioning
confidence: 99%
“…Because many bacteria use atrazine as a nitrogen source (Udiković-Kolić et al 2012), the addition of carbon may enhance atrazine degradation in soils where the amount of available carbon, rather than nitrogen, is limiting growth. Several studies have shown that bioaugmentation with Pseudomonas citronellolis ADP harboring the atzABCDEF genes enhance atrazine degradation in topsoil (Chelinho et al 2010;Lima et al 2009). Bioaugmented P. citronellolis is capable of atrazine degradation at 12°C (Monard et al 2008), but no studies explored its exploitation in subsoil.…”
Section: Introductionmentioning
confidence: 99%